Correlation of Thrombocytopenia and Length of Hospitalization in Dengue Child Patient - Riyadi Adrizain; Ananda Hanifah Husna; Andri Rezano (Universitas Islam Bandung, 2020)
Dengue virus infection (DVI) is one of the major health problems that cause 500 thousand patients hospitalized annually. Thrombocytopenia is one of the abnormal hematologic findings that is always found in DVI patients. This study aimed to determine the correlation of thrombocytopenia and length of hospitalization in dengue child patients. This retrospective analysis study used secondary data from seven major hospitals in Bandung with a total sampling method. The inclusion criteria were patients aged 0–18 years old diagnosed with dengue fever (DF), or dengue hemorrhagic fever (DHF), or dengue shock syndrome (DSS) who was admitted from January to December 2015 and excluded when there was comorbid as well as incomplete data. The correlation was analyzed by Spearman’s rank correlation test. There were 2,025 samples from a total of 5,712 DVI cases during 2015. Among those who admitted, most of the patients experienced severe thrombocytopenia (40%) with the average length of hospitalization was 4.84 days. This result was not much different from the patients with moderate (38.1%) and mild (21.9%) thrombocytopenia who were treated for an average of 4.13 days and 4.08 days, respectively. The analysis of correlation obtained a significant relationship between thrombocytopenia and length of hospitalization despite showing a weak correlation (r=0.231, p=0.001). In conclusion, there is a weak correlation between thrombocytopenia and length of hospitalization among dengue child patients. KORELASI TROMBOSITOPENIA DENGAN LAMA RAWAT INAP PADA PASIEN ANAK TERINFEKSI VIRUS DENGUEInfeksi virus dengue (IVD) merupakan salah satu masalah kesehatan utama yang menyebabkan 500 ribu pasien dirawat di rumah sakit setiap tahun. Trombositopenia adalah salah satu temuan abnormal hematologi yang selalu ditemukan pada pasien IVD. Penelitian ini bertujuan mengetahui korelasi trombositopenia dengan lama rawat inap pada pasien anak terinfeksi virus dengue. Penelitian analitik retrospektif ini menggunakan data sekunder tujuh rumah sakit besar di Kota Bandung dengan metode total sampling. Kriteria inklusi adalah pasien anak usia 0–18 tahun yang didiagnosis demam dengue (DD), atau demam berdarah dengue (DBD), atau sindrom syok dengue (SSD) yang dirawat dari bulan Januari hingga Desember 2015. Kriteria eksklusi meliputi komorbiditas dan data rekam medis yang tidak lengkap. Analisis dilakukan dengan uji korelasi rank Spearman. Terdapat 2.025 sampel dari total 5.712 kasus IVD selama tahun 2015. Di antara yang dirawat, sebagian besar pasien mengalami trombositopenia berat (40%) dengan lama rawat inap rerata 4,84 hari. Hasil ini tidak jauh berbeda dengan pasien dengan trombositopenia sedang (38,1%) dan ringan (21,9%) yang dirawat selama rerata 4,13 hari dan 4,08 hari masing-masing. Analisis korelasi diperoleh hubungan yang bermakna antara trombositopenia dan lama rawat inap meskipun dengan nilai korelasi lemah (r=0,231; p=0,001). Simpulan, terdapat korelasi lemah antara trombositopenia dan lama rawat inap pada pasien anak terinfeksi virus dengue.